Carcinoma Cuniculatum Masquerading as Eumycetoma: An Unacquainted Entity Posing a Diagnostic Dilemma - Pooja SHARMA; Pragya JAIN; Ankur GARG; Sonal SHARMA (Türk Patoloji Dergisi, 2025)
Carcinoma cuniculatum (CC) is a rare and distinct clinicopathological variant of well-differentiated squamous cell carcinoma. It is a rare and slow-growing tumor with a peculiar infiltrative growth pattern resembling rabbit burrows (cuniculi). It usually occurs over the plantar aspect of the foot but can also occur at other sites like the oral cavity and genitals. The pathogenesis is unknown, with various hypotheses of trauma as proposed by different authors. It is essential to be aware of this entity as it commonly mimics benign and other low-grade squamous cell carcinoma (SCC). Diagnosis of CC can be challenging and requires repeated histological evaluation and clinical correlation. Herein, we present a case report of CC of the plantar and dorsal aspect of the foot in a 60-year-old male with a history of multiple chronic non-healing ulcers, which was clinically suspected as eumycetoma and remained inconclusive on numerous biopsies.